Stochastic Traffic-Based Fatigue Life Assessment of Rib-to-Deck Welding Joints in Orthotropic Steel Decks with Thickened Edge U-Ribs - Junlin Heng; Kaifeng Zheng; Sakdirat Kaewunruen; Charalampos Baniotopoulos (Applied Sciences, 2019)
Rib-to-deck (RD) joints in orthotropic steel decks (OSDs) are highly prone to fatigue cracking under heavy traffic. An innovative longitudinal rib, named the thickened edge U-rib (TEU), has been proposed to enhance the fatigue strength of RD joints and validated through model tests. However, more studies are still required on the effect of TEUs in real engineering applications. To this end, a typical OSD bridge in China has been investigated, based on the experimental results. In the analysis, a stochastic traffic model is employed to simulate the vehicle-induced fatigue actions comprehensively. The framework of the stochastic model is proposed by considering the randomness in both the vehicles and their lateral distribution. Then the traffic model is instantiated using standard truck models in conjunction with the codes of practice as well as the observed data. A multi-scale finite element model is later established to determine the stochastic stress responses, whereas the influence surface method is used to improve computational efficiency. In this study, Monte Carlo simulations have been carried out to derive the stress spectra for the RD joints at different critical locations. Based on the test data and the derived spectra, an engineering assessment has been performed to obtain the fatigue life of RD joints in OSDs with and without TEUs, respectively. The new findings show that the position of joints has a remarkable influence on the stress spectra of RD joints, which results in the notable difference in fatigue life of the joints. Further, the fatigue life of RD joints can be significantly prolonged by using TEUs, and the prolongation rates are varied from 141% to 161% depending on the calculation methods and traffic models used.